2011
DOI: 10.1016/j.fct.2010.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Cob(I)alamin reacts with sucralose to afford an alkylcobalamin: Relevance to in vivo cobalamin and sucralose interaction

Abstract: Vitamin B 12 , chemically known as cobalamin, is a complex organometallic cofactor associated with several cobalamin-dependent enzymes. Its reduced form, cob(I)alamin, is one of the most powerful nucleophiles known. Following reduction of hydroxocobalamin (OH-Cbl) by sodium borohydride, cob(I)alamin was shown to react readily with sucralose (1',6'-dichloro-1',6'-dideoxy-β-Dfructofuranosyl-4-chloro-4-deoxy-α-D-galactopyranoside; a synthetic sweetener) in an aqueous system to form an alkylcobalamin (Suc-Cbl). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Some compounds may also react directly with compounds that are key for cell function. For example, as halogens are leaving groups, halogenated aliphatics my react with endogenous or exogenous nucleophiles, including DNA and proteins (Motwani et al 2011), affecting the efficiency of biological processes.…”
Section: Biomassmentioning
confidence: 99%
“…Some compounds may also react directly with compounds that are key for cell function. For example, as halogens are leaving groups, halogenated aliphatics my react with endogenous or exogenous nucleophiles, including DNA and proteins (Motwani et al 2011), affecting the efficiency of biological processes.…”
Section: Biomassmentioning
confidence: 99%
“…In an in vitro study using human liver cells, sucralose was found to react with cob(I)alamin, a reduced form of vitamin B 12 , forming alkylcobalamin (Suc-Cbl), and it was suggested that such reactions, may affect the cobalamin levels, analogous to exposure to epoxides and nitrous oxide [11]. Moreover, sucralose has raised concerns as a possible human health hazard, mostly in public media, because of its chlorinated structure [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…The most representative of these is methionine synthase (MetH), ,, which is responsible for the regeneration of methionine from homocysteine. Other examples involve methanol-dependent cobalamin or corrinoid/Fe–S protein. , Another key function played by cob­(I)­alamin is the biosynthesis of adenosylcobalamin (AdoCbl), in a process guided by ATP:corrinoid adenosyltransferases (ACAs). The pivotal role of cob­(I)­alamin is also revealed in reductive dehalogenation of halogenated compounds, a process involved in dehalorespiration in several anaerobic bacteria. Finally, the reactions with N 2 O, NO, NO 2 – , NO 3 – , sucralose, epoxides, and SO 2 – have also been explored, adding to the diversity of processes that rely on the super-reduced form of vitamin B 12 . …”
Section: Introductionmentioning
confidence: 99%